20000 (NLXE POD WODOJs - Verne, Jules (Leningrad (NmOLODAQ gWARDIQs, 1935)
(Nw (B1870 (NGODU(B, (NPOSLE MU^ITELXNYH POISKOW GEROQ(B, (NNAZWANIQ(B, (NS@VETA(B, (NSTILQ PROIZWEDENIQ(B, (Nv@LX wERN NAPE^ATAL ROMAN (B"(NdWADCATX TYSQ^ LXE POD WODOJ(B". (NiZ RODIW[EGOSQ W (B1865 (NGODU PERWOGO ZAMYSLA (B"(NpUTE[ESTWIQ POD WODOJ(B", (NSTAW[EGO SPERWA (B"(NpUTE[ESTWIEM POD WOLNAMI OKEANA(B", (NZATEM (B"(NdWADCATX@ PQTX@ TYSQ^AMI LXE POD MORQMI(B" (NI(B, (NNAKONEC(B, "(NdWADCATX@ TYSQ^AMI LXE POD WODOJ(B", (NW SOZNANII PISATELQ WOZNIK OBRAZ nEMO(B. (Na (B"(NnAUTILUS(B" - (N\TO BOLEE ^EM PROSTO PODWODNAQ LODKA(B, (NO SU]ESTWOWANII KOTORYH UVE ZNAL v(B.(NwERN(B. "(NnAUTILUS(B" (NKAPITAN nEMO (B- (N\TO PERWAQ (B"(NGRAVDANSKAQ PODWODNAQ LODKA(B", (NPROOBRAZ APPARATOW DLQ ISSLEDOWANIQ MORSKIH GLUBIN(B.s
Keywords: Adventure; Classics; Fiction; Science Fiction